PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS III SDN 125 PEKANBARU - Gustavia, Yuli Gustavia Yuli; Marhadi, Hendri Marhadi Hendri; ', Lazim Lazim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The background of this research is the low learning outcomes Social Sciences student, with an average grade 67.1. Based on the problems appear researchers conducted a study entitled "Application of Cooperative Learning Model Numbered Heads Together (NHT) to improve student learning outcomes Elementary School third grade 125 Pekanbaru. The research was conducted on March 11, 2015 until May 13, 2015 with 3 cycles. The subjects were students of class III Elementary School 125 Pekanbaru totaling 21 people who used the data source. Data collection instruments in this thesis is the teacher and student activity sheets and learning outcomes. This study presents the results of learning derived from the value of daily tests before treatment with an average of 67.1%, an increase in the first cycle with the average being 71.7%. In the second cycle increased by an average of 68.5% and an increase in the third cycle with an average of 82.3%. The activities of teachers in the learning process in cycle 1 the first meeting and the second meeting of the 70.8% increase to 75%. Second cycle of the first meeting and the second meeting of the 79.1% increase to 83.3%. In the third cycle of the first meeting and the second meeting of the 91.7% increase to 95.8%. data analysis activities of students in the first cycle the first meeting with an average of 62.5% and a second meeting to increase to 70.9%. Second cycle of the first meeting and the second meeting of the 79.2% increase to 83.3%. In the third cycle of the first meeting and the second meeting of the 87.5% increase to 95.8%. Based on these results Application of Cooperative Learning Model Numbered Heads Together (NHT) can increase student learning outcomes Elementary School third grade 125 Pekanbaru.Key Words: Cooperative Learning Model Numbered Heads Together (NHT), Sosial Studies Student’s Achievement